Out-of-hospital cardiac arrest: determinant factors for immediate survival after cardiopulmonary resuscitation - Daniela Aparecida Morais; Daclé Vilma Carvalho; Allana dos Reis Correa (Universidade de São Paulo, 2014)
OBJECTIVE: to analyze determinant factors for the immediate survival of persons who receive cardiopulmonary resuscitation from the advanced support units of the Mobile Emergency Medical Services (SAMU) of Belo Horizonte.METHOD: this is a retrospective, epidemiological study which analyzed 1,165 assistance forms, from the period 2008 - 2010. The collected data followed the Utstein style, being submitted to descriptive and analytical statistics with tests with levels of significance of 5%.RESULTS: the majority were male, the median age was 64 years, and the ambulance response time, nine minutes. Immediate survival was observed in 239 persons. An association was ascertained of this outcome with "cardiac arrest witnessed by persons trained in basic life support" (OR=3.49; p<0.05; CI 95%), "cardiac arrest witnessed by Mobile Emergency Medical Services teams" (OR=2.99; p<0.05; CI95%), "only the carry out of basic life support" (OR=0.142; p<0.05; CI95%), and "initial cardiac rhythm of asystole" (OR=0.33; p<0.05; CI 95%).CONCLUSION: early access to cardiopulmonary resuscitation was related to a favorable outcome, and the non-undertaking of advanced support, and asystole, were associated with worse outcomes. Basic and advanced life support techniques can alter survival in the event of cardiac arrest.